Aile Hekimliği Sistemi için Covid-19 Yönetim Önerileri - İzzet Fi̇dancı; Hilal Aksoy; Duygu Ayhan Başer (Journal of Contemporary Medicine, 2020)
Birinci basamak çalışanları, yeni bir durum olan covid-19'un yayılmasını önlemek için büyük bir sorumluluğa sahiptir. Sağlık sisteminin iyi işlemesi için birinci basamak sağlık hizmetleri daha fazla kullanılmalıdır. Yazımızda sağlık sisteminin bloke olmasını önleme önerilerimizi paylaştık.Dear Editor,Primary preventive healthcare services have alwaysbeen the easiest and fastest way for the patientto accesshealthcare services. In addition to the emergencydepartments, these centers come to mind first to bereferred in case of pandemics.[1] Primary healthcarepersonnel undertake a great responsibility in this newand special case of Covid-19 viral pandemic. The basisfor the emergency action plan should be established bytaking necessary measures in these primary healthcarecenters and easing the workload in order to prevent abottleneck in the health system.Necessary equipment should be provided, or diagnosiscenters should be established so that Covid-19 viruscan be diagnosed through all primary preventivehealthcare services. People should stay in isolatedenvironments as much as possible and the contagionrisk for the virus should be minimized in order to easethe workload of hospitals and to take the pandemicunder control. It is clear that the delayed diagnosisof people infected with the virus increase the risk ofgetting infected. In countries where family healthcaresystem runs properly, a good planning and designationof family healthcare centers as the basis for emergencyaction plans to minimize the riskof infection couldhelp limiting the contagion areas.[2] Cities should beseparated into regions and isolated. Healthcare needsother than urgent ones should be met by the familyhealthcare center in order to minimize the risk forcontagion and to ease the workload of hospitals toprevent a bottleneck in the health system.Family healthcare centers should employ Covid-19diagnosis kits[3] giving fast results. However, they arenot being as valid and reliable as PCR (polymerasechain reaction) diagnosis methods.[4] Patient referralsystem should operate without any compromise inorder to minimize the risk for contagion. The bordersof small areas in cities should be determined and asingle-family healthcare center should be designatedto each region to limit the virus.We believe that primary preventive healthcare servicesalways forming the first and basic step of healthcaresystems should be well-organized and publiccooperation should be ensured to limit Covid-19 viralpandemic. It would be helpful in terms of minimizingloss of life until vaccine and medicine studies provetheir success.